2017
DOI: 10.1002/macp.201700414
|View full text |Cite
|
Sign up to set email alerts
|

A Prerequisite of the Poly(ε‐Caprolactone) Self‐Induced Nanohybrid Shish–Kebab Structure Formation: An Ordered Crystal Lamellae Orientation Morphology of Fibers

Abstract: The shish–kebab structure has been extensively applied in many fields; however, the formation mechanism is still an open question. In this study, different electrospun poly(ε‐caprolactone) (PCL) fibers are applied as the shish material in a self‐induced crystallization process, and two different self‐induced crystal structures are obtained. The PCL fibers with an ordered crystalline morphology lead to an induced crystalline structure with the crystal lamellae perpendicular to the fiber axis. However, the PCL f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…It has been previously demonstrated that for PCL kebabs the kebab size and period increase as incubation time increases. , However, BCP crystal growth could be quite different from PCL homopolymer, and desired crystalline morphology can only be formed when crystallization instead of BCP phase separation dominates the structure formation process. For PCL- b -PAA BCP kebabs, incubation times ranging from 0.5 to 10 min were tested for their effect on NFSK morphology, as seen in Figure . PCL electrospun nanofibers had an average diameter of 351 ± 177 nm (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously demonstrated that for PCL kebabs the kebab size and period increase as incubation time increases. , However, BCP crystal growth could be quite different from PCL homopolymer, and desired crystalline morphology can only be formed when crystallization instead of BCP phase separation dominates the structure formation process. For PCL- b -PAA BCP kebabs, incubation times ranging from 0.5 to 10 min were tested for their effect on NFSK morphology, as seen in Figure . PCL electrospun nanofibers had an average diameter of 351 ± 177 nm (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…The kebabs competed to grow in a limited space, which would cause distortion. Wang et al found that ordered PCL nanofibers formed a regular SK structure, while disordered nanofibers led to a complex crystal layer morphology …”
Section: Resultsmentioning
confidence: 99%
“…26−28 When nanofibers and the polymer matrix are similar in geometry, such as lattice parameters, orientation, or some crystal plane spacing, polymer chains can form a kebab or coating on the surface of nanofibers. 29,30 Yu et al confirmed that the crystallization behavior of polymers significantly increased the proliferation and alkaline phosphatase (ALP) activity of MC3T3-E1 cells. 31 Chen et al found that the SK structure improved the mechanical properties of nanofibrous membranes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shish-kebab crystal morphology was reported for PCL/CNT electrospun nanocomposite systems. [105,106] Arras et al [106] firstly demonstrated the formation of NHSK in electrospun PCL/MWCNT composite. The MWCNT, which is shish in their case, is overgrown by lamellae polymer crystals (kebabs).…”
Section: Homopolymer-based Compositesmentioning
confidence: 99%